Making the invisible visible - Coetzer, Diane (My University, 2015)
No abstract provided.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Arts by Creative Writing to the Faculty of Humanities, School of Literature, Language and Media, University of the Witwatersrand, 2015
Keywords: English fiction-21st century